(untitled) (Materiali di Estetica. Terza serie, 2022)
The paper examines the question of the symbolic dimension in the political. It is argued that both Ernesto Laclau’s and Claude Lefort’s Post-Marxist accounts understand this question as a problem of rethinking symbolic unity. I will trace arguments of these accounts and examine their relation to Carl Schmitt’s notion of the political. To this end, both aesthetic and politico-juridical dimensions of the political are discussed by focusing on two questions: 1) How should it be understood that in Laclau’s idea of populism the symbolic construction of the people differs from the juridical construction of the people? 2) What does it mean to understand symbolic unity as political power as Lefort does?